Euthanasia in veterinary medicine - Aşkın Yaşar (Eurasian Journal of Veterinary Sciences)
Euthanasia is the most fascinating and the most discussed issue in ethics. Euthanasia is a rarely applicable veterinary medical action that it should be performed by specially trained personnel on the desperated animals suffering from a cureless disease or so aged and result in rapid unconsiousness followed by cardiac or respiratory arrest and ultimate loss ot brain function. The term "euthanasia" is a conjucted word derived from Greek terms "eu" meaning "good" and "thanatos" meaning "death" Still, there are two ways of euthanasia, as active and passive methods in application bul the active one is perterred in veterinary practice.